(untitled) (Research, Society and Development, 2020)
Although social movements have, to a certain extent, achieved some democratization of spaces, this is not recurrent and has become an issue in the struggle for inclusive policies, especially in gender issues. The study aims to analyze the importance of family farming and agroecology in promoting and maintaining equity and gender emancipation from the experiences of settlers from the Osvaldo de Oliveira Sustainable Development Project (PDS), located in Macae/RJ. The research problem is how the different actions carried out by the agroecological movement carried out in the PDS have an impact on the process of politicization and emancipation of women who reside in the settlement. The methodology consists of a literature review, analysis of federal legislation, official documents and speeches presented by the movement on its website on the technological tool of agroecology and open interviews with settled women. As a result, it was verified that, the struggle assumed by the rural women’s movements, act on two main fronts: the demand for agrarian reform and differentiated agricultural policies for family farmers, as well as specific demands for access and maintenance of specific rights. It is concluded that, although the women seated in the PDS Osvaldo de Oliveira are encouraged to become agents of social transformation and protagonists of their life and political history, there are still difficulties arising from sexist issues, especially in the leadership capacity and place of speaks to the demands aimed at enshrining women’s rights.